Reliability-Based Design of Solid and Nail-jointed I-Section of Nigerian-Grown African Birch (Anogeissus leiocarpus) Timber Column - U.N. Wilson; A.A. Adedeji; F.O.P. Oriola; J.A. Alomaja; J.E. Sani (Journal of Applied Sciences and Environmental Management)
The Nigerian-grown African birch timber was used to assemble I- section specimens which were tested in the laboratory for their compressive strengths. Solid square sections of the same specie were similarly tested for an apt comparison of results. A structural reliability analysis was carried out for these two sections to ascertain their performance as structural timber columns using statistical parameters that were determined for the deterministic design of the timber column. A FORTRAN-based program was also developed and used for the reliability analysis of the Nigerian-grown African birch columns designed to ascertain their level of safety using First-Order Reliability Method (FORM). The ‘I’- section was found unsafe to bear the design load unlike its corresponding solid section. An identified I- section of (100 x 400mm) was found adequate (with Pf =1.22 x 10-02) whose compressive resistance corresponds to (200 x 100mm) of the solid section (with Pf =7.76 x 10-02) which is practically half the dimension of the I-section. This shows that the solid section has a capacity twice that of the ‘I’- section of equal dimensions. However, considering the minimum dimension of the of the two sections capable of supporting the design load, the ‘I’- section is more economical than the solid section since it offers a less effective area of 11,200mm2 compared to the solid section with an effective area of 20,000mm2 . The ‘I’-section also showed a higher capacity to bear the Euler load with greater lengths than the solid section because of its greater radius of gyration and rigidity value and would be rather preferable for long columns than the solid section. Considering the limited availability of larger dimensions of solid sections, the built-up I- section would be more relevant where large sized sections are required.